The discomfort zone how leaders turn difficult conversations into breakthroughs - Reynolds, Marcia (San Francisco : Berrett-Koehler Publishers, 2014)
"Leaders, coaches, and mentors are charged with helping others to stretch their limits. However, few people enjoy hearing the messy--and sometimes painful--feedback it takes to overcome a personal obstacle. Marcia Reynolds shows how to use the discomfort zone to help others grow, not suffer"-- |c Provided by publisher.
Keywords: Leadership; Personal coaching; Mentoring; Oral communication; BUSINESS & ECONOMICS / General